Audit Energi Listrik Gedung Tower 1 Institut Teknologi Sepuluh Nopember Surabaya - Moch Ilham Syafiq; Aris Heri Andriawan; Izzah Aula Wardah (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
Tower 1 at Institut Teknologi Sepuluh Nopember Surabaya is a high-rise building (High Risk Building) in the education and office sectors, experiencing an annual increase in energy consumption. Therefore, regular and thorough energy audits are necessary to save electricity consumption and ensure that usage aligns with the Indonesian Ministry of Energy and Mineral Resources Regulation No. 13 of 2012. An energy audit is a method to calculate the energy consumption level of a building and determine potential energy savings through energy conservation. The Electrical Energy Consumption Intensity (IKE) is used as a parameter to determine whether the building's energy consumption is efficient or wasteful. The initial energy audit of Tower 1 was conducted quantitatively with on-site measurements over one year, covering the building's electrical system and area. The measurements indicated that the IKE of Tower 1 is 50.86 kWh/m²/year. Subsequently, the total installed electrical energy consumption load was calculated, yielding an IKE of 166.15 kWh/m²/year. Based on the initial energy audit results, energy conservation measures were recommended, including upgrading the lighting system with higher lumen lamps and adjusting air conditioning (AC) to the established standards. Implementing these recommendations resulted in an increased IKE of 176.04 kWh/m²/year, which is still considered efficient compared to the ASEAN-USAID standard of 240 kWh/m²/year.